Abortion Due to Neospora caninum in Dairy Cattle in Southern Santa Catarina State, Brazil - Costa, Leonardo Silva da; Pena, Hilda Fátima Jesus; Withoeft, Jessica Aline; Cristo, Thierry Grima de; Melo, Isadora Cristina; Oliveira, Solange; Moura, Anderson Barbosa; Casagrande, Renata Assis (Acta Scientiae Veterinariae, 2021)
Background: Neosporosis is a cosmopolitan disease known as the main infectious cause of abortion in cattle, reported in several states in Brazil. The transplacental transmission in cattle is responsible for perpetuating the disease in the herd. In the state of Santa Catarina, previous studies on this protozoan in cattle are mostly serological surveys. To increase information about this reproductive disorder, this work describes the diagnosis of abortions due to Neospora caninum in dairy cattle from state of Santa Catarina and the follow-up for 4 years in a farm affected by neosporosis. Case: From 2015 to 2019, necropsy was performed on 10 aborted bovine fetuses, between fifth and eighth month of pregnancy, with 1 fetus aborted in 2015, 3 in 2016, 2 in 2017 and, 4 in 2019, all originating from the same dairy property in the southern region of state of Santa Catarina. No macroscopic lesions were found. Histopathology revealed mild to moderate multifocal mononuclear necrotizing encephalitis in 5 fetuses, and multifocal mild mononuclear myositis and myocarditis in 4 and 3 fetuses, respectively. Polymerase Chain Reaction (PCR) using primers based on the Nc-5 gene was positive for N. caninum in five fetuses. Three visits were performed in the farm for epidemiological evaluation and blood samples collection for IgG antibodies anti-N. caninum (IFAT). The total herd was 170 Jersey, Holstein and crossbred cattle, raised in a semi-confined system with mechanical milking system. Since 2014, there has been a significant increase in abortions cases, approximately 20 cows had abortions; in the year 2015, approximately 10; in 2016, less than 5; in 2017, 4 cows aborted; in 2018, 11 abortions and, in 2019, there were 4 abortions. An increase in the rate of return to estrus was also reported, and both primiparous and multiparous cows had reproductive disorders. Abortions were recorded throughout the year and occurred predominantly between the fourth and sixth month of pregnancy. In 2016, an Indirect Immunofluorescence Reaction (IFAT) was performed on sera from 26 cows (13 with a history of reproductive disorders and another 13 without disorders). Of these, 50.0% (13/26) were seropositive, with titers ranging from 100 to 1600 (cutoff ≥100). The Enzyme Immunoassay (ELISA) of the entire herd was carried out in 2017, with 26.54% (43/162) of seropositivity, 8.02% (13/162) suspect, and 30.4% (17/56) had reproductive disorders. It was observed that only animals born on the property were used for replacement, there was less possibility of direct contact between dogs on the property with milking facilities, placental and fetal remains, properly disposing of these, incinerating or burying. Thirty animals were discarded from the property, 25 of which had reproductive disorders. All young female daughters of seropositive cows remained on the property for replacement. During the evaluation period, all dogs were eliminated. Discussion: In this study, the diagnosis of neosporosis was made through epidemiology, histopathological lesions characterized by mononuclear encephalitis, myocarditis and myositis, and detection of the agent by PCR, associated with serological techniques. The lesions observed are indicative of N. caninum infection and are compatible with lesions observed in other studies. Serological screening is important to complement the diagnosis of abortion by N. caninum and to help control the agent in herds. From this report it is concluded that N. caninum is an important agent of reproductive disorders in cattle in the southern region of Santa Catarina, the different serological analyzes showed a good screening index for the inclusion of control strategies. In addition, the monitoring of reproductive rates of affected properties becomes necessary over the years, allowing better observation of control strategies. Keywords: reproductive disorder, fetal death, protozoan, parasitology. Descritores: distúrbio reprodutivo, morte fetal, protozoário, parasitologia.